The effect of additives with essential oils on the productivity of young pigs - K. M. Syrovatko; V. S. Vuhliar (Regulatory Mechanisms in Biosystems, 2021)
Modern feed additives based on natural plant components are increasingly used as an alternative to synthetic antibiotics in animal nutrition. Phytobiotics are natural plant components that are increasingly gaining demand for use in ready-to-eat animal feed and provide proper health and microflora of the body. A scientific and economic experiment was conducted in order to determine their effect on the productivity of young pigs. We composed three groups of analogues each comprising 12 individuals, which were formed in a 15-day equalization period. According to the results of the study on the use of a new feed factor protein-vitamin-mineral supplement Efiprot in the diets of young pigs, a positive effect was observed on increase in the average daily weight gain by 4.1% and 7.1% compared with the control group. There was also seen a better absorption of nutrients in the diet compared with the control indicator. During inclusions of essential oil in the diet of the pigs, we observed an increase in the digestibility of nutrients: in particular, the level of digestibility of dry and organic matter increased in the second and third experimental groups, as well as digestible protein and digestibility of crude fat was better in the first experimental group than in the control group. During the study, there was a tendency towards better breakdown of sparingly soluble carbohydrates under the action of feed additives compared with the control indicator. Thus, the use of protein-vitamin-mineral supplement during the rearing of young pigs not only increased the efficiency of their rearing, but also led to better digestion and maintenance of the microflora of the gastrointestinal tract.